X-linked inhibitor of apoptosis protein (XIAP) inhibition in systemic sclerosis (SSc) - Bergmann, Christina; Hallenberger, Ludwig; Chenguiti Fakhouri, Sara; Chenguiti Fakhouri, Sara; Merlevede, Benita; Brandt, Adrian; Dees, Clara; Zhu, Honglin; Zehender, Ariella; Zhou, Xiang; Schwab, Annemarie; Chen, Chih-Wei; et al. (Annals of the Rheumatic Diseases, 2021)
X-linked inhibitor of apoptosis protein (XIAP) is a multifunctional protein with important functions in apoptosis, cellular differentiation and cytoskeletal organisation and is emerging as potential target for the treatment of various cancers. The aim of the current study was to investigate the role of XIAP in the pathogenesis of systemic sclerosis (SSc). The expression of XIAP in human skin samples of patients with SSc and chronic graft versus host disease (cGvHD) and healthy individuals was analysed by quantitative PCR, immunofluorescence (IF) and western blot. XIAP was inactivated by siRNA-mediated knockdown and pharmacological inhibition. The effects of XIAP inactivation were analysed in cultured fibroblasts and in the fibrosis models bleomycin-induced and topoisomerase-I-(topoI)-induced fibrosis and in Wnt10b-transgenic mice. The expression of XIAP, but not of other inhibitor of apoptosis protein family members, was increased in fibroblasts in SSc and sclerodermatous cGvHD. Transforming growth factor beta (TGF-β) induced the expression of XIAP in a SMAD3-dependent manner. Inactivation of XIAP reduced WNT-induced fibroblast activation and collagen release. Inhibition of XIAP also ameliorated fibrosis induced by bleomycin, topoI and overexpression of Wnt10b in well-tolerated doses. The profibrotic effects of XIAP were mediated via WNT/β-catenin signalling. Inactivation of XIAP reduces binding of β-catenin to TCF to in a TLE-dependent manner to block WNT/β-catenin-dependent transcription. Our data characterise XIAP as a novel link between two core pathways of fibrosis. XIAP is overexpressed in SSc and cGvHD in a TGF-β/SMAD3-dependent manner and in turn amplifies the profibrotic effects of WNT/β-catenin signalling on fibroblasts via transducin-like enhancer of split 3. Targeted inactivation of XIAP inhibits the aberrant activation of fibroblasts in murine models of SSc.
CRIS-Team Scopus Importer:2021-05-07
Keywords: fibroblasts; pulmonary fibrosis; scleroderma; systemic